Changes in absolute gravity 2000–2015, South Island, New Zealand. Issue 1 (2nd January 2016) - Bilham, Roger; Niebauer, Tim; Pearson, Chris; Molnar, Peter
ABSTRACT: We quantify changes in gravity that have occurred over the past 15 years at 14 points between latitudes 42.5°S and 44°S in the South Island of New Zealand. Ten of the points form two transects across the Southern Alps and four lie in the epicentral region of the 2010 Canterbury earthquakes. At each location gravity was measured using an absolute gravimeter (FG5–111) with a nominal accuracy of 1 µGal. Observed changes in gravity varied from −53 to +43 µGal in the presence of surface elevation changes in the range −11 cm to +20 cm. Despite the difficulty in quantifying gravitational contributions from surface and subsurface water, uplift in both the Southern Alps and the Christchurch region is consistent with a Bouguer surface gradient of approximately 1.97 µGal cm –1, appropriate for the mean density of crustal rocks.